2022
DOI: 10.1128/spectrum.01045-22
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalis -Induced Macrophage Necroptosis Promotes Refractory Apical Periodontitis

Abstract: Oral infectious diseases represent a major neglected global population health challenge, imposing an increasing burden on public health and economy. Refractory apical periodontitis (RAP), mainly caused by Enterococcus faecalis , is a representative oral infectious disease with considerable therapeutic challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…It is well recognized that P. intermedia and P. gingivalis are closely related in dental biofilms and that their co-colonization is associated with chronic periodontitis [30]. Additionally, refractory periapical periodontitis or persistent root canal infections may be associated with E. faecalis [31,32]. According to the OD600 value and the agar diffusion experiments shown in Figure 5a,b, larger quantities of CHX were associated with a stronger inhibitory capability.…”
Section: Discussionmentioning
confidence: 91%
“…It is well recognized that P. intermedia and P. gingivalis are closely related in dental biofilms and that their co-colonization is associated with chronic periodontitis [30]. Additionally, refractory periapical periodontitis or persistent root canal infections may be associated with E. faecalis [31,32]. According to the OD600 value and the agar diffusion experiments shown in Figure 5a,b, larger quantities of CHX were associated with a stronger inhibitory capability.…”
Section: Discussionmentioning
confidence: 91%
“…Interference with E. faecalis -modulated host cell responses may help to treat RAP. In vivo experiments demonstrated that inflammation and bone destruction were alleviated in RIPK3-deficient mice with E. faecalis -induced RAP [ 113 ]. Moreover, the CASP-1 inhibitor partly suppressed bone resorption in an experimental RAP rat model [ 114 ].…”
Section: E Faecalis -Modulated Host Cell Responsesmentioning
confidence: 99%
“…Yang et al, 2022). In E. faecalis-infected AP, the deletion of RIPK3 resulted in a significant reduction of inflammatory markers such as IL-6, IL-1β, and TNF, while periapical bone density was increased (Dai et al, 2022). Moreover, local knockdown of RIPK3 in F. nucleatuminfected AP was associated with decreased inflammatory cytokines and decreased bone loss (J.…”
Section: Necroptosis: a New Therapeutic Target For Apmentioning
confidence: 99%